A STRATEGI PEMBIAYAAN PENDIDIKAN DASAR DAN MENENGAH DI ERA PANDEMI COVID 19: SEKOLAH SWASTA - Marinu Waruwu (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
The objective of this study is to examine the strategy of financing education in private schools. Based on research conducted by researcher, studies on education financing strategies during the Covid-19 pandemic have not been widely carried out. The research method was conducted through literature studies from national and international journals, government policy documents, and books. Data analysis used qualitative descriptive approach. The results of the study show that the strategy of financing education during the Covid 19 pandemic mostly goes well with the policy alignments from the government through internet data quota assistance, affirmation and performance School Operational Assistance, scholarships, wage subsidies, and Single Tuition in universities. However, there are several schools, especially private schools that have difficulty paying teacher's salary, teacher welfare declines, and parents who are late paying educational management contribution. The strategy for education financing solutions during the COVID-19 pandemic is that government policies in the form of assistance to students and parents need to be continued, consistency of budget planning by schools, use of budgets that prioritize priority scales, and transparency and accountability in the management of education financing.